Misconceptions identification on biodiversity and protist using multiple choice open reason (mcor) - Yunanda, Intan; Susilo, Herawati; Ghofur, Abdul (Biosfer: Jurnal Pendidikan Biologi, 2019)
This research aims to identify misconceptions of Biodiversity and Protist material. This type of research is a quantitative descriptive study. The sampling technique is purposive sampling with the provisions that misconceptions have not been identified, and students have received Biodiversity and protists. The object of the research is the students of class XI SMA Islam Malang, SMAN 1 Trenggalek, MAN 2 Lamongan, and SMAN 1 Pare, each in one class with a total of 127 students. Retrieval of data using a diagnostic instrument in the form of multiple-choice open reason (MCOR) with a total of 15 questions about Biodiversity and 15 questions about Protist. The results showed the average of misconceptions of 22,08% experienced by students on Biodiversity and the mean of misconceptions of 13,25% experienced by students on Protist. The highest misconception occurred in the threat indicator of biodiversity damage that is equal to 35,91%. Whereas for Protist, the highest misconception occurred in the sub-indicator identification of the general characteristics of Protist like an animal that is 26,28%. The conclusion is the misconception on the material of Biodiversity and Protist, including misconception type 2 or Mi-2, that is, students answer incorrectly to the core questions and are accompanied by the right reasons. A suggestion from the research that has been done is that it is necessary to develop a level three diagnostic instrument used by experts to find out students' misconceptions so that the results are more detailed. Besides, it is necessary to identify the causes of misconceptions and identify misconceptions in student handbooks on Biodiversity and Protist.